The role of a school nurse in the care of a child with diabetes mellitus type 1 - the perspectives of patients and their parents: Literature review - Stefanowicz Anna; Stefanowicz Joanna (Slovenian Journal of Public Health, 2018)
The aim of this literature review was to explore the views of parents and children with type 1 diabetes mellitus regarding having a school nurse.